2009
DOI: 10.1101/gad.1742509
|View full text |Cite
|
Sign up to set email alerts
|

Polycomb protein Ezh2 regulates pancreatic β-cell Ink4a/Arf expression and regeneration in diabetes mellitus

Abstract: Proliferation of pancreatic islet b cells is an important mechanism for self-renewal and for adaptive islet expansion. Increased expression of the Ink4a/Arf locus, which encodes the cyclin-dependent kinase inhibitor p16INK4a and tumor suppressor p19 Arf , limits b-cell regeneration in aging mice, but the basis of b-cell Ink4a/Arf regulation is poorly understood. Here we show that Enhancer of zeste homolog 2 (Ezh2), a histone methyltransferase and component of a Polycomb group (PcG) protein complex, represses I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
352
3
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 342 publications
(366 citation statements)
references
References 41 publications
10
352
3
1
Order By: Relevance
“…Loss of polycomb function in a variety of cell types leads to upregulated transcription of the negative regulators of the cell cycle encoded by the Ink4/Arf locus (Cdkn2a/Cdkn2b) (11,33,34). Cdkn2a and Cdkn2b are not normally expressed in the developing cerebral cortex (35)(36)(37), and we found the H3K27me3 modification present on the Cdkn2a and Cdkn2b promoters in the wild-type E12 cortex (Fig.…”
Section: Loss Of Prc2 Function Results In Up-regulated Gene Expressiomentioning
confidence: 98%
“…Loss of polycomb function in a variety of cell types leads to upregulated transcription of the negative regulators of the cell cycle encoded by the Ink4/Arf locus (Cdkn2a/Cdkn2b) (11,33,34). Cdkn2a and Cdkn2b are not normally expressed in the developing cerebral cortex (35)(36)(37), and we found the H3K27me3 modification present on the Cdkn2a and Cdkn2b promoters in the wild-type E12 cortex (Fig.…”
Section: Loss Of Prc2 Function Results In Up-regulated Gene Expressiomentioning
confidence: 98%
“…This hypothesis is supported by our functional assays in BRIN cells showing that loss of H3K27me3 leads to reactivation of the silent state. A previous study reported reduction of H3K27me3 repressive mark at the Ink4a/Arf locus in mouse β-cells, with age, that leads to increased expression (35). This was associated with a decline of the histone methyltransferase Ezh2 with age (35).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, ageing de-represses this locus, leading to increased levels of cell cycle inhibitors (p16 cip1 and p19), decreased B-lymphoma Moloney murine leukaemia virus insertion region-1 (BMI1) banding [135] and decreased levels of enhancer of zeste homologue 2 (EZH2) [136], a histone methyltransferase and member of the polycomb group of proteins.…”
Section: Old Agementioning
confidence: 99%